2022
DOI: 10.1088/2053-1591/ac5cae
|View full text |Cite
|
Sign up to set email alerts
|

Effects of viscoelastic bonding layer on performance of piezoelectric actuator attached to elastic structure

Abstract: In the context of the finite elements analysis, the mechanical performance of viscoelastically bonded smart structures is investigated and analyzed. Three different models are considered and compared. In the 1st model, the actuator is glued to the host structure. On the other hand, in the two other models the actuator is glued to the bonding layer which is glued to the host structures. To explore the effect of the bonding layer characteristics on the mechanical behavior of the host structure, both elastic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Many researchers [20][21][22][23][24][25] applied the finite element analysis to achieve different analyses about the viscoelastic behavior in different topics such as the dynamic response of orthotropic viscoelastic composite laminates plate, impact response of viscoelastic-frictionless bodies, Dynamic response of viscoelastic functionally graded porous thick beam and the analysis of viscoelastic bonding layer on the behavior of piezoelectric actuator.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers [20][21][22][23][24][25] applied the finite element analysis to achieve different analyses about the viscoelastic behavior in different topics such as the dynamic response of orthotropic viscoelastic composite laminates plate, impact response of viscoelastic-frictionless bodies, Dynamic response of viscoelastic functionally graded porous thick beam and the analysis of viscoelastic bonding layer on the behavior of piezoelectric actuator.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, concrete beams have been used for damage evaluation in reinforced concrete structures with lap splices of tensional steel bars [ 32 ]. Additionally, the effectiveness of PZT actuators has been examined when combined with viscoelastic bonding layers on elastic structures [ 33 ]. In some cases, researchers have evaluated the performance of surface-bonded piezoelectric sensors and actuators on host structures, considering factors such as adhesive layer effects and non-uniform thickness, through FE simulations [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the latest studies, piezoelectric materials adhesively bonded to structures were also found in some other cases such as in composite patches [26] which is used to evaluate the vibration excitation and separation in laminates and concrete beams which is used for damage evaluation of reinforced concrete structures at lap splices of tensional steel bars [27]. Additionally, the performance of PZT actuators was found in the effects of a viscoelastic bonding layer bonded to an elastic structure [28]. In some cases, surface-bonded piezoelectric sensors and actuators' performance on the host structures has been evaluated for PZT itself using FE simulations to check the adhesive layer effects, including non-uniform thickness [29].…”
Section: Introductionmentioning
confidence: 99%